2013
DOI: 10.1093/pcp/pct071
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance Responses in Ripening Berries of Vitis vinifera L. cv Muscat Hamburg

Abstract: 21 22 23 24 25 C LR-E LR-E+K LR-W LR-W+K 22,32c 23,22abc 23,07bc 24,25a 24,20ab) %

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
96
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 96 publications
17
96
1
Order By: Relevance
“…This is in agreement with general observations by viticulturists that moderately warm temperatures favor sugar accumulation during ripening [21,112,114] leading to wines higher in alcohol in warm climates and seasons. In a previous study on fruiting cuttings ABA levels were significantly increased by high temperature after 45 but not after 14 days of post-véraison heat treatment [38]. This is consistent with our results where the repression of ABA synthesis genes in berries at véraison is inversed at the more developed stages.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with general observations by viticulturists that moderately warm temperatures favor sugar accumulation during ripening [21,112,114] leading to wines higher in alcohol in warm climates and seasons. In a previous study on fruiting cuttings ABA levels were significantly increased by high temperature after 45 but not after 14 days of post-véraison heat treatment [38]. This is consistent with our results where the repression of ABA synthesis genes in berries at véraison is inversed at the more developed stages.…”
Section: Resultssupporting
confidence: 93%
“…Similar categories were shown to be modified by temperature in a previous study with fruiting cuttings [38]. The short heat stress period of 2 h in the present study presumably enhanced the induction of these transcripts in which over-expression was not observed with longer temperature treatments in other studies where plants started to adapt to their changed conditions [66-68].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Yan et al (2014) isolated a full-length MBF1 cDNA sequence (VvMBF1) from V. vinifera 3 Vitis amurensis that was up-regulated in the leaves of grape plants following both drought and abscisic acid treatments. Carbonell-Bejerano et al (2013) reported that berry MBF1a and MBF1c were up-regulated under high temperature when grape 'Muscat Hamburg' plants growing from cuttings were exposed to two different environmental regimes, 20°C/15°C (day/night) and 30°C/25°C (day/night), at the onset of ripening (veraison). Wang and Li (2006a) reported that exogenous SA pretreatment decreased thiobarbituric acidreactive substances content and relative electrolyte leakage in grape leaves under heat stress, indicating that SA can induce intrinsic heat tolerance in grape.…”
Section: Some Important Transcript Factors Could Be Involved In Heat mentioning
confidence: 99%
“…Transcriptomic analysis of grape leaves under heat stress and subsequent recovery showed that the effect of heat stress and recovery on grape appears to be associated with multiple processes and mechanisms, including stress-related genes, transcription factors, and metabolism (Liu et al, 2012). Carbonell-Bejerano et al (2013) revealed that the establishment of a thermotolerance response in berries under high temperatures was marked by the induction of HSPs and the repression of transmembrane transporter-encoding transcripts using the GrapeGen GeneChip. George et al (2015) reported on proteome changes in cv Cabernet Sauvignon grape cells exposed to sudden high-temperature stresses, with more than 2,000 proteins identified and quantified using spectral counting of the entire data set.…”
mentioning
confidence: 99%